2018
DOI: 10.2166/wpt.2018.037
|View full text |Cite
|
Sign up to set email alerts
|

Phycoremediation of textile wastewater using indigenous microalgae

Abstract: The recognition that environmental pollution is a worldwide threat to public health and environmental degradation has given rise to new initiatives for environmental restoration for both economic and ecological reasons. There are several methods to treat the dye contaminated industrial wastewater; of which biological treatment methods are economical and environmentally friendly. The bacteria and fungi remediation of dye pollutants has been well characterized over a period of more than 30 years. So, finding oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…These results are also consistent with the recent studies by T. A. Aragaw and others, who recorded the spectra of raw and activated BP, matching with the spectra in the present study. 48–50…”
Section: Resultsmentioning
confidence: 99%
“…These results are also consistent with the recent studies by T. A. Aragaw and others, who recorded the spectra of raw and activated BP, matching with the spectra in the present study. 48–50…”
Section: Resultsmentioning
confidence: 99%
“…The optimum pH level for removal Direct Blue 71 and Disperse Red 1 by Chlorella vulgaris was found to be at 8 1 . Increasing in pH from 6 to 8 caused important proliferation in the rate of removal dye with indigenous microalgae 11 .…”
Section: Resultsmentioning
confidence: 99%
“…The treatment by microalgae diminishes the color and nutrient load of textile effluent, which diminishes numerous negative environmental influences 10 . Indigenous microalgae have undeniably the potential to rapidly, efficiently, and effectively eliminate dyes in wastewater to acceptable ranges of guide line limits at ambient temperature and neutral pH range 11 . Microalgae, which have been widely cultivated in wastewater treatment, have the ability to remove nutrients from a wide range of wastewater types, including industrial wastewater 12,13 .…”
mentioning
confidence: 99%
“…The advantages of biological processes include environmental compatibility, competitive cost, non-hazardous metabolites, and reduced water consumption [19]. In recent times, microalgae and cyanobacteria have emerged as sustainable remedies for eliminating harmful substances present in various wastewater types, such as agricultural runoff [20], domestic wastewater [21], agroindustrial wastewaters [22][23][24][25], and landfill leachate [26]. It was reported that Cosmarium species could attenuate malachite green dye at temperatures of 5-45 • C and pH 9, demonstrating its ability to treat wastewater containing this pollutant [27].…”
Section: Introductionmentioning
confidence: 99%